Dynamics of contraceptive use among schedule caste women in Uttar Pradesh - Singh, Mahesh Nath; Joshi, Niyati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Scheduled caste is socially and economically disadvantaged population and contributes to one fifth of India’s population. Population policy (2002), government of India, has set the task of addressing unmet need for contraception in order to achieve the medium term objective of bringing the total fertility rate down to replacement level by the year 2010. Methods: The data used for the paper has been taken from Reproductive and Child Health (RCH) Survey round-II (2001-02) phase-I of Uttar Pradesh. Information of only scheduled caste women has been used for analysis. Bi-variate and logistic regression analysis was carried out. Results: There is positive relationship between knowledge of traditional methods, level of education and standard of living; which is expected to have inverse relationship. Use of contraceptive methods among these groups of women is substantially low, but it follows an expected trend. Government health care institutions remain the main source of contraception for scheduled caste women in the study area. Conclusions: Results from the logistic analysis give a clear picture that women with the information/knowledge are more likely to use the method in the near future.